2020
DOI: 10.1111/iwj.13437
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐epidermal moisture measurement: an evidence‐based approach to the assessment for early evidence of pressure ulcer presence

Abstract: This paper aims to discuss the literature pertaining to early pressure‐shear induced tissue damage detection, with emphasis on sub‐epidermal moisture measurement (SEM). The current method for pressure detection is visual skin assessment (VSA); however, this method is fraught with challenges. Advances in early detection of pressure ulcers are reported in the literature and mainly involve measuring inflammation markers on weight‐bearing anatomical areas in order to capture the first signs of tissue damage. One n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The first is that the SEM Scanner enables early identification of tissue damage and enables practitioners to provide improved anatomically specific interventions [71]. The second is that this early and appropriate intervention of non-visible pressure-induced tissue damage prevents sub-cellular damage from progressing and manifesting itself on the surface of the skin as a diagnosed visible Stage I PI [62]. Based on these findings, further research is being conducted to investigate the outcomes of these targeted interventions at specific anatomies, in addition to observational studies comparing the SEM scanner to other current measures of PI progression such as ultrasound, temperature, and pain.…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is that the SEM Scanner enables early identification of tissue damage and enables practitioners to provide improved anatomically specific interventions [71]. The second is that this early and appropriate intervention of non-visible pressure-induced tissue damage prevents sub-cellular damage from progressing and manifesting itself on the surface of the skin as a diagnosed visible Stage I PI [62]. Based on these findings, further research is being conducted to investigate the outcomes of these targeted interventions at specific anatomies, in addition to observational studies comparing the SEM scanner to other current measures of PI progression such as ultrasound, temperature, and pain.…”
Section: Key Resultsmentioning
confidence: 99%
“…Particularly, ongoing clinical studies and published work by the Bates-Jensen group at the University of California in Los Angeles indicate the clinical significance of SEM in the early detection of PIs[23,24,55,58,59]. Collectively, these studies contributed to SEM being identified as an important biomarker of PI etiology[1,23,24,37,47,53,54,[60][61][62][63][64][65].…”
mentioning
confidence: 99%
“…The progression of cell death and tissue necrosis causes gradual local alterations of the mechanical properties of the injured tissues that can, in turn, change the distributions of strains and stresses in forms that are likely to exacerbate the evolving injury, for example, through development of inflammatory oedema and localised rigour mortis in skeletal muscles 65,69,75,120‐122 . Localised inflammatory oedema, one of the earliest signs of cell death in PUs/PIs, may be detectable via measurement of a biophysical marker called the biocapacitance of tissues 15,121‐132 . Reperfusion that follows a period of prolonged ischaemia may further increase the extent of tissue damage as it involves release of damaging oxygen free radicals 95‐100,133 …”
Section: Tissue Damage Due To Mechanical Loading Repair and Individua...mentioning
confidence: 99%
“…65,69,75,[120][121][122] Localised inflammatory oedema, one of the earliest signs of cell death in PUs/PIs, may be detectable via measurement of a biophysical marker called the biocapacitance of tissues. 15,[121][122][123][124][125][126][127][128][129][130][131][132] Reperfusion that follows a period of prolonged ischaemia may further increase the extent of tissue damage as it involves release of damaging oxygen free radicals. [95][96][97][98][99][100]133 The microclimate between the skin and the support surface or any skin-contacting medical device or object plays an important role in the development of PUs/PIs.…”
Section: Tissue Damage Due To Mechanical Loading Repair and Individua...mentioning
confidence: 99%
“…(11) In addition, ultrasonic equipment requires considerable space and is expensive; thus, its usage is limited. Subcutaneous moisture meters can be used for the early diagnosis of pressure ulcers, (12) but their operation inevitably affects diagnosis accuracy. Therefore, high-precision and economical test methods for the early diagnosis of pressure ulcers should be developed.…”
Section: Introductionmentioning
confidence: 99%